Expression genetics identifies spinal mechanisms supporting formalin late phase behaviors - Ritchie Jennifer; Zheng Ming; Sahbaie Peyman; Li Xiangqi; Peltz Gary; Mogil Jeffrey S; Clark J David (SAGE Publishing, 2010)
Abstract Background Formalin injection into rodent hind paws is one of the most commonly employed pain assays. The resulting nocifensive behaviors can be divided into two phases differing in timing, duration and underlying mechanisms. Spinal sensitization has long been felt to participate in the second phase of this response, although this sensitization is incompletely understood. By using correlative analysis between spinal gene expression and mouse strain-dependent intensity of late phase behavior, we hypothesized genes participating in variability of the response could be identified. Results Late phase formalin behavior scores among 10 inbred mouse strains were correlated with a spinal cord gene expression database constructed using expression arrays. Messenger RNA levels for several genes were highly correlated with the late phase behavioral responses. Most of these genes had already been implicated in mechanisms regulating pain and analgesia. One of the most strongly correlated genes, Mapk8 coding for c-Jun N-terminal kinase 1 (JNK1), was chosen for further analysis. Studies using additional strains of mice confirmed that spinal cord mRNA expression levels of Mapk8 followed the pattern predicted by strain-specific levels of formalin behavior. Interestingly, spinal cord JNK1 protein levels displayed an inverse relationship with mRNA measurements. Finally, intrathecal injections of the selective JNK inhibitor, SP600125, selectively reduced late phase licking behavior. Conclusions Wide differences in pain behaviors, including those resulting from the injection of formalin, can be observed in inbred strains of mice suggesting strong genetic influences. Correlating levels of gene expression in tissues established to be mechanistically implicated in the expression of specific behaviors can identify genes involved in the behaviors of interest. Comparing formalin late phase behavior levels with spinal cord gene expression yielded several plausible gene candidates, including the Mapk8 gene. Additional molecular and pharmacologic evidence confirmed a functional role for this gene in supporting formalin late phase responses.